'Athletes for Peace'? From the Quest to Hold the Mavericks Accountable to a Second American Rebel Tour of South Africa. Issue 8 (15th July 2022) - Sikes, Michelle M.; Fredericks, Jacob J.; Rodríguez, Paulina A.; Macedo, Emmanuel; Poorman, Michael; Lyons, Matthew; Pandit, Rucha; Dyreson, Mark
ABSTRACT: In 1988 a team of American track and field athletes violated international bans against competing in apartheid South Africa. Their trek created a global firestorm of controversy. Critics including white and Black US and South African athletes condemned the 'rebels' as at best naïve dupes but more commonly as immoral mercenaries. The 'rebels' defended themselves on the grounds that they were exercising 'athletes rights' and wanted to see the South Africa situation firsthand rather than kowtowing to athletics administrators. As the 'rebels' returned to the US, The Athletics Congress, the US body that oversaw track and field, held a series of trials and sentenced the members of the South African tour to long suspensions. A defiant group of 'rebels' fought their suspensions. About half of the original group, reinforced by new recruits, returned to South Africa for a 1989 tour as national and international debates about their activities raged.